The Implementation of the Utawi Iki-Iku (Pegon Symbols) Formula Method in Basic Syntax Courses at Islamic Higher Education - Sirad, Mochamad Chobir; Rusyadi, Refki; Choiruddin, Choiruddin; Sulaiman, Sulaiman (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This study aimed to find out the implementation of the utawi iki-iku (Pegon symbols) formula method in basic syntax (nahw) courses in Islamic higher education. This study used a qualitative approach with a type of phenomenological study to understand and explain the phenomenon of the research subjects. The techniques of data collection in this study used in-depth interviews with 4 respondents with certain criteria as well as tests on students’ learning outcomes in terms of giving i’rab and reading Yellow Books through three stages of tests. The results of this study showed that the implementation of the Pegon symbol formula method in basic nahw courses at Islamic higher education began by the planning stage that all students re-perceived the lessons they had learned; the process stage in nahw learning used the classical Arabic Pegon method by reading the contents of the book; and the post-teaching stage referred to the evaluation in away that the students read one by one in front of the class to find out their abilities to use Arabic Pegon. Then, the impact of the Pegon symbol formula method in basic nahw courses was shown by the increase in students’ abilities to give i’rab and read Yellow Books revealed from the test and depth interviews with the students.